Teacher beliefs and practices in emergencies: Is COVID-19 the demise of Early Childhood Development? - Nomatter Manzunzu; Joyce Maera (IGI Global, 2023)
Teachers' practices are usually determined by their beliefs and cultural dispositions. To this end, teachers' beliefs and practices in emergencies have an effect on their day-to-day discharge of duties. This chapter establish whether teachers' beliefs and practices can spell the demise of Early Childhood Development (ECD) or not. In addressing this, a qualitative case approach was adopted. Five ECD teachers in three schools were purposively selected, observed and interviewed. Teachers` fears of Covid-19 were observed and these influenced their practices. Teachers were less prepared to handle ECD learners. Further, learners did not have adequate Personal Protective Equipment (PPEs) such as masks. Use of alternative teaching methods such as online learning emerged though they need to be well supported by the government.